Release: Aboriginal Sculpture Will Be Commissioned - External Relations, University of Regina (External Relations, University of Regina, 2004)
First Nations University of Canada, the University of Regina and its Alumni Association, and three levels of government are working together to award the largest-ever aboriginal sculpture commission in Canada. Staff no